2021
DOI: 10.56093/ijas.v91i1.110952
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of baby corn (Zea mays) cultivation in Haryana

Abstract: Maize (Zea mays L.) is used for human food as well as animal feed, and it is also widely used in starch industry. Towards diversification and value addition through cultivation of Baby corn for vegetable purpose is emerging as a highly profitable activity. Farmers can grow four crops in a year, and the production of baby corn generates employment amongst the rural poor’s, from children to the elderly persons. The demand for baby corn is rapidly increasing in urban areas of India. Keeping in view the importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The economic evaluation of baby corn has been evaluated by RAM et al (2021), in Haryana/India, and the authors have observed the high profitability in the exploration of this product when considering the production costs of 111,480 rupees ha -1 and return of 142,451 rupees ha -1 . This information reinforces the economic viability of baby corn exploration, which may be a viable alternative for small family producers mainly because of the early harvest and decrease in the use of raw materials when compared to crops for grain production (SANTOS et al 2014).…”
Section: Results and Discussion Agronomic Performance Of Maize Cultiv...mentioning
confidence: 99%
“…The economic evaluation of baby corn has been evaluated by RAM et al (2021), in Haryana/India, and the authors have observed the high profitability in the exploration of this product when considering the production costs of 111,480 rupees ha -1 and return of 142,451 rupees ha -1 . This information reinforces the economic viability of baby corn exploration, which may be a viable alternative for small family producers mainly because of the early harvest and decrease in the use of raw materials when compared to crops for grain production (SANTOS et al 2014).…”
Section: Results and Discussion Agronomic Performance Of Maize Cultiv...mentioning
confidence: 99%